THE CONTRIBUTION OF LIBRARIANS IN SUPPORTING THE LEARNING PROCESS IN HIGHER EDUCATION THROUGH THE DEVELOPMENT OF SYNERGIC AND DYNAMIC SOCIAL INTERACTION - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The research aims to describe the contribution of librarians in supporting the learning process in higher education. The research aims at careful scrutiny with analysis based on detailed comprehensive studies, dominating the main content, which is based on the contribution of librarians in supporting the learning process in higher education. Research has a scope of study, fundamental analysis based on the focus of the main topic, regarding the contribution of librarians to support the learning process in tertiary institutions. Research analysis requires critical thinking, in order to apply a concept to history in the past or is happening. Therefore it is very appropriate to use historical approach research, characterized by the dominance of a critical inquiry into the development of a thought or term. Primary information sources, namely the most important element, are used as primary data. Collection of historical approach data prioritizes the empowerment of library research through a variety of reading activities on the literature, subject to the contribution of librarians, information services, learning processes in higher education. Research uses qualitative descriptive analysis, sourced from various theoretical reading material research, research and non-research. Research dominates the description, checking and evaluative of factual facts in order to produce solutions to the problems that arise in the phenomenon of the role of librarians supporting the learning process in higher education. For the sake of validity of the analysis, content analysis is needed, useful in analyzing the meaning of the most important concepts, namely the contribution of librarians to support the success of the learning process. Observation of activities in the library, empowered to construct the theory. The use of comparative analysis is useful in making comparisons before and after the development of libraries in supporting the vision and mission of higher education to reach World Class University. The results showed that librarians have a very large contribution and play an active role in supporting the learning process in higher education.